2020
DOI: 10.3390/medicina56070344
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Aspects and Cortical Auditory Maturation in Children with Cochlear Implants

Abstract: Background and objectives: The cochlear implant is not only meant to restore auditory function, but it also has a series of benefits on the psychomotor development and on the maturation of central auditory pathways. In this study, with the help of neuropsychological tests and cortical auditory potentials (CAEPs), we intend to identify a series of instruments that allow us to monitor children with a cochlear implant, and later on, to admit them into an individualized rehabilitation program. Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Similar to Cochlear implantation, where there is basically no age limit, given that the youngest worldwide implanted child was less than 6 months of age, and especially since research showed the importance of early auditory rehabilitation on neurodevelopmental aspects and cortical auditory maturation in CI children. 28 Despite or rather because of the age limit of 5 years or older for the here investigated BB and the long-term…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similar to Cochlear implantation, where there is basically no age limit, given that the youngest worldwide implanted child was less than 6 months of age, and especially since research showed the importance of early auditory rehabilitation on neurodevelopmental aspects and cortical auditory maturation in CI children. 28 Despite or rather because of the age limit of 5 years or older for the here investigated BB and the long-term…”
Section: Discussionmentioning
confidence: 91%
“…Similar to Cochlear implantation, where there is basically no age limit, given that the youngest worldwide implanted child was less than 6 months of age, and especially since research showed the importance of early auditory rehabilitation on neurodevelopmental aspects and cortical auditory maturation in CI children. 28 Despite or rather because of the age limit of 5 years or older for the here investigated BB and the long‐term proven efficacy and audiological benefit, our study aimed to compare the satisfaction and quality of life after intervention (invasive vs. noninvasive). Especially, since the research in the past years focused on improving and understanding language and speech perception in children with hearing loss, 2 , 3 , 4 , 5 , 6 , 7 with no studies exploring the impact on the quality of life in children with a Bonebridge or an Adhear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CI not only restores auditory function, but also plays an important role in cognitive development. 37,38 Due to the limitation in the sample size of the present study, new studies with larger and multicentric samples are required, because the results of the present sample varied according to the commitment of each patient regarding CI use. Therefore, new studies are needed to make new advances in hearing rehabilitation in patients with other associated disabilities.…”
Section: Discussionmentioning
confidence: 97%
“…Studies 37 38 have shown that the CI also helps in the development of cognitive skills (general development). It has been observed that children with hearing loss show improvements in their understanding, concentration, sequential processing, and working memory, with almost normal values.…”
Section: Discussionmentioning
confidence: 99%